Impact of Metabolic Factors on the Incidence and Intensity of Knee Osteoarthritis in a Sample of Iraqi Patients - Mohammed Mahmood Mohammed (Journal of Global Pharma Technology, 2018)
Background: Osteoarthritis (OA) is a leading cause of physical disability, morbidity and lessened quality of life, mainly in elderly people. It characterized by inflammation, breakdown, and consequent loss of cartilage of the joints. OA usually associated with obvious risk factors, like obesity, age, inflammation and joint injury, in addition to quality of diet and some metabolic factors. Purpose: To evaluate the role of obesity and different metabolic factors on the incidence and severity of symptoms in patients with knee osteoarthritis. Methods: Fourth patients with painful knee OA were randomly selected at the outpatient clinic of Baghdad teaching hospital. All patients diagnosed with OA in one or both knee joints. The patients were allocated into two groups: Group A: Include 20 non-obese patients diagnosed with knee OA. Group B: Include 20 overweight and obese patients diagnosed with knee OA. A validated, self-administered questionnaire method known as Western Ontario Mac Master Osteoarthritis Index (WOMAC) which includes evaluation of pain, stiffness and physical function, were done. FBG, TC, LDL, TG, HDL cholesterol, in addition to serum leptin, IL-1β and TNF-α were measured for both groups to be statistically evaluated. Results: The results showed a significant differences (P<0.05) between group A and group B regarding to BMI, serum leptin, TG, LDL, IL-1β and TNF-α (less values in group A), in addition to WOMAC score and serum HDL (more values in group A). However, no significant differences (P<0.05) seen for FBG and TC between both groups. Conclusion: This study clearly demonstrated that increasing body weight with the presence of other metabolic factor can strongly enforce and accelerate many process involved in the pathogenesis of OA, including inflammatory response, cartilage degradation and bone remodeling.Keywords: Osteoarthritis, Obesity, Metabolic syndrome, inflammation, WOMAC.